Information Technologies, A New Global Division of Labor, And the Concept of Information Society - Kocikowski, Andrzej (My University, 2010)
Utilizing the “old” economical theory of Marx and its conceptual apparatus, we indicate a possibility of decomposition of capitalistic economic and political systems; the decomposition can be brought about by new global division of labor. We make an attempt at proving the existence of exact correspondence of the ICT revolution and the efficiency (productivity) of the knowledge production process; the latter has been tied to general laws of the "old" theory, that is the issue of migration and especially concentration of capital. We propose a new way of looking at the issue of the so-called Information Society.
Keywords: Global division of labor; Information Society; ICT; Production of knowledge; Productivity; Marx